2017
DOI: 10.1002/2017jf004311
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution sub‐ice‐shelf seafloor records of twentieth century ungrounding and retreat of Pine Island Glacier, West Antarctica

Abstract: Pine Island Glacier Ice Shelf (PIGIS) has been thinning rapidly over recent decades, resulting in a progressive drawdown of the inland ice and an upstream migration of the grounding line. The resultant ice loss from Pine Island Glacier (PIG) and its neighboring ice streams presently contributes an estimated ∼10% to global sea level rise, motivating efforts to constrain better the rate of future ice retreat. One route toward gaining a better understanding of the processes required to underpin physically based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 107 publications
0
19
0
Order By: Relevance
“…Apart from an open marine gateway for ice into Pine Island Bay, a force is needed to push the ice mélange into the bay. Iceberg trajectories are predominantly steered by currents and wind (Death et al, 2006). Therefore, a water exchange from the ice-shelf cavity across the bathymetric ridge would support flushing the trapped icebergs westward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from an open marine gateway for ice into Pine Island Bay, a force is needed to push the ice mélange into the bay. Iceberg trajectories are predominantly steered by currents and wind (Death et al, 2006). Therefore, a water exchange from the ice-shelf cavity across the bathymetric ridge would support flushing the trapped icebergs westward.…”
Section: Discussionmentioning
confidence: 99%
“…Brisbourne et al, 2014). Two expeditions over the past decade have collected bathymetry data beneath Pine Island Glacier from autonomous underwater vehicles, but the data are limited to the vicinity of widely spaced survey lines and only cover a small fraction of the cavity area (Jenkins et al, 2010;Davies et al, 2017). Here we present continuous multibeam bathymetry data from the newly exposed area at the front of PIG together with satellite synthetic aperture radar (SAR) and optical imagery and use this unique combination of highly resolved data to investigate the role of the pinning point and other bathymetric features in the calving development of the PIG ice shelf.…”
Section: Introductionmentioning
confidence: 99%
“…The consistent presence of broad but vertically thin subglacial cavities appears to challenge a purely melt-driven model of future ice sheet collapse, as access by warm water to the grounding line would be hampered by the thin cavity (Schoof, 2007). This physical limitation is supported by models for Pine Island Glacier margin, which indicated that cavities < 200 m thick slowed the ingress of warm bottom water over topographic ridges (De Rydt et al, 2014). More complex fully coupled ice-ocean models also show the development of thin cavities and indicate that the associated weak circulation acts to slow grounding line retreat relative to that predicted by an uncoupled model (Seroussi et al, 2017).…”
Section: Two Ice Shelf Populationsmentioning
confidence: 99%
“…Direct measurements of sub-ice-shelf bathymetry by seismic spot measurements is slow and often impractical due to 45 the extremely crevassed environment (Brisbourne et al, 2014;Rosier et al, 2018). Exploration of sub-ice-shelf cavities using autonomous underwater vehicles can also be risky and time consuming to attain regional coverage (Jenkins et al, 2010;Davies et al, 2017). An alternative technique to provide a first-order estimate of the bathymetry is the inversion of airborne gravity anomaly data, which can be collected quickly and efficiently over large areas.…”
Section: Introduction 25mentioning
confidence: 99%